What Drives Different Types of Capital Flows and Their Volatilities in Developing Asia? - Rogelio Mercado; Cyn-Young Park (Asian Development Bank (ADB), 2011)
Understanding the determinants of capital inflows is essential to designing an effective policy framework to manage volatile capital flows and their disruptive potential. This paper aims to identify factors that explain the size and volatility of various types of capital flows to developing Asia with regard to other emerging market economies. The estimates for a panel dataset show that per capita income growth, trade openness, and change in stock market capitalization are important determinants of capital inflows to developing Asia. Trade openness increases the volatility of all types of capital inflows, while change in stock market capitalization, global liquidity growth, and institutional quality lowers the volatility. A regional factor plays an important role in determining the size and volatility of capital inflows in emerging Europe and merging Latin America, suggesting that regional economic cooperation and policy coordination may be an important element in designing a policy framework to manage capital inflows in merging economies.
hdl:11540/2026
Keywords: F21; F32; F36; 330; capital flows; volatility of capital flows; panel data; developing Asia; push and pull factors